Leveraging integrated youth services for social prescribing: a case study of Youth Wellness Hubs Ontario - Turpin, Aaron; Chiodo, Deb; Talotta, Maria; Henderson, Jo (My University, 2024)
Introduction: Integrated youth services (IYS) presents a unique opportunity to adopt social prescribing (SP) strategies within the IYS service model by developing and leveraging a highly connected multidisciplinary network of clinical and community-based service providers to tackle health inequities and enhance service access and outcomes for youth. This paper outlines a case study of Youth Wellness Hubs Ontario (YWHO), Canada, a collective of youth-serving organizations integrated and networked, and operating as a learning health system implementing SP services. The main study objective was to document how YWHO hubs engage in social prescribing through service provision. Methods: We adopted an embedded case study approach. Data were collected from youth (n = 6361) aged between 12 and 25 years who were seeking services at a YWHO hub. Descriptive analyses, including frequencies across categories, were generated from service data, including reason for visit, needs addressed and service provided. Results: A comparative analysis of services requested and provided found that youth across visits to YWHO hubs were engaging with multiple services and service providers, with a wide range of health, mental health and social support needs being addressed. Conclusion: YWHO implements SP services that aim to improve mental health resilience by supporting the vocational, educational and socialization needs of young people accessing IYS through YWHO hubs.
Keywords: social prescribing; integrated youth services; youth services; youth well-being